Strategy Identification For Sustainable Key Performance Indicators Delivery Process For Scholarly Publication and Citation - Dhillon, Sharanjit Kaur; Ibrahim, Roliana; Selamat, Ali (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Key Performance Indicator (KPI) is one of the performance measurement tools that assist someone in monitoring their performance against the target set by the management. Despite many implementations in delivering the KPIs, they are still unable to perform. It would involve investigating the current strategies undertaken by the management on how they deliver KPIs to academic staff in the Research Alliance of K-Economy (RAKE). This paper aims to investigate the problems of non-achieving KPI targets among academic staffs of RAKE. It also aims to highlight four areas of the strategy implementation that can be developed to deliver improved publication and citation outcomes for the targets set. The literature is reviewed and the targeted respondents extensive experience in the issues related to scholarly publication and citation is drawn on. The four areas of strategic implementation are discussed as a guide. The paper finds that the imposed strategies can be applied to achieve the targets set by management if initiatives are taken by all levels of academic staffs as well as the involvement by the top management of the institution. The paper has immediate practical benefits for academic staffs of RAKE that it provides a four steps guide for improving the publication and citation culture among the RAKE staffs by utilizing knowledge management. This will result in greater outcome for the management of the University in maintaining the status as a Research University (RU) in Malaysia. It can be concluded that the strategies imposed can be applied at the beginners level. Existing work has produced a sustainable KPI delivery process framework using Viable System Model (VSM) where it shows that there is a need to have integration among the university databases. However, this framework does not highlight details on how knowledge management contributes to the strategic initiatives of successful KPI delivery process.